Postoperative prophylactic intermittent noninvasive ventilation versus usual postoperative care for patients at high risk of pulmonary complications: a multicentre randomised trial. (January 2023) - Abrard, Stanislas; Rineau, Emmanuel; Seegers, Valerie; Lebrec, Nathalie; Sargentini, Cyril; Jeanneteau, Audrey; Longeau, Emmanuelle; Caron, Sigrid; Callahan, Jean-Christophe; Chudeau, Nicolas; Beloncle, François; Lasocki, Sigismond; et al.
Abstract: Background: Pulmonary complications are an important cause of morbidity and mortality after surgery. We evaluated the clinical effectiveness of noninvasive ventilation (NIV) in preventing postoperative acute respiratory failure. Methods: This is an open, multicentre randomised trial that included patients at high risk of postoperative pulmonary complications after elective or semi-urgent surgery with an Assess Respiratory Risk in Surgical Patients in Catalonia (ARISCAT) score ≥45. Patients were randomly assigned to intermittent prophylactic face-mask NIV for 6–8 h day −1 or usual postoperative care. The primary outcome was in-hospital acute respiratory failure within 7 days after surgery. Patients who underwent surgery and postoperative extubation were included in the modified intended-to-treat analysis. Results are presented as n (%) and odds ratios (ORs) with 95% confidence intervals. Results: Between November 2017 and October 2019, 266 patients were randomised and 253 included in the main analysis. Of these, 203 (80.2%) were male with a mean age of 68 (11) yr and an ARISCAT score of 53 (6); 237 subjects (93.7%) underwent cardiac or thoracic surgery. There were 125 patients allocated to prophylactic NIV and 128 to usual care. Unplanned treatment termination occurred in 58 subjects in the NIV group, which was linked to NIV discomfort for 36 subjects. There was no difference in the incidence of the primary outcome of postoperative acute respiratory failure between treatment groups (NIV: 30 of 125 subjects [24.0%] vs usual care: 35 of 128 subjects [27.3%]; OR 0.97 [0.90–1.04]; P =0.54). Conclusions: Prophylactic NIV was difficult to implement after high-risk surgery because of low patient compliance. Prophylactic NIV did not prevent acute respiratory failure. Clinical trial registration: NCT 03629431 and EudraCT 2017-001011-36.